UPAYA PENGEMBANGAN MUATAN LOKAL DI SMP SE KABUPATEN KULON PROGO - FARIDA HANUM (Universitas Negeri Yogyakarta, 2005)
Abstract The objectives of this research was to find an illustration on the implementation of the local content in Junior Secondary School in the Regency of Kulon Progo and the effort of those schools in developing the local content programs. This is a survey research. The respondents of the research were all Public Junior Secondary School principals, teachers, and students, with a sample consisted of 12 schools, each representing of a district. The data were collected by using open questionnaires, interview observation. The data were analyzed descriptive qualitative. The research results indicate that (1) the student’s choice of local content available in every Public Junior Secondary School in Kulon Progo, varying according to the school’s condition, especially the availability of teachers in each school. Very seldom the school provides special teacher for local content program. Therefore, choices of local content made by students could seldom be met by the school. School funding is the main reason why students demand is not granted if the available teachers are not able to teach the program requested. (2) In fact the potential local content which could be develop in the area ssuch as farming, planting and other hand work in construction and handycraft were not provided yet. But those demand mostly could not be implemented in schools due to teachers constrain. The school had not made cooperation with students parents or local residents who might be able to teach local content. (3) most students wish that the local content be a vocational life skill for their future job such as lesson on a computer, food science, dress making. Considering to the economic status of the students parents in Kulon Progo’s Junior High Schools were relatively unable to provide funding for further study of their children, then it is necessary to study and rearrange lessons of local content given to the schools. For that reason, attention of Kulon Progo Education Department Representative especially the department of curriculum is highly expected to give their attention on this matter. Keywords:local content, junior secondary school